CARBON STOCKS IN PHYTOMASS OF WOODY PLANTS AND COARSE WOODY DEBRIS IN OLD-GROWTH BLUEBERRY PINE FORESTS IN THE NATURAL RESERVE “KIVACH” - A. N. Pekkoev; S. A. Moshnikov; I. V. Romashkin; D. V. Teslya (Вопросы лесной науки)
The study presents the results of the research on permanent test plots established in 2023 in 180-190-year-old bilberry-type pine forests growing on sandy soils on the test site of the first type of level intensity «Kivach» (Republic of Karelia, middle taiga subzone). The calculated data of phytomass and carbon (C) stock in the pools of stand, undergrowth, undergrowth phytomass, as well as in coarse woody debris (CWD) is presented. The obtained data of the stand phytomass and its C stock was analyzed by four different methods and the results were compared. In pine forests the stock of stand phytomass calculated based on the regional data varies from 171 to 395 t ha-1 and averages 254.2 t ha-1, whereas its C stock varies from 85 to 197 t C ha-1 with an average value of 126.5 t C ha-1. The obtained results are by 7–10% lower than those obtained using other methods, which indicates the need for an additional research. Under the forest canopy, the undergrowth is represented mainly by pine and spruce and only sometimes with a minor participation of birch. The total undergrowth density varies from 0.2 to 4.9 thousand pcs ha-1. Undergrowth is often absent or represented by an insignificant amount of common rowan or grey alder. The total C stock of undergrowth and undergrowth fluctuates from 0.2 to 2.3 t C ha-1, that is only 0.57% of the phytomass C pool. The C stock in CWD in the studied pine forests varies from 9 to 60 m3 ha-1 and averages 40 m3 ha-1. The largest share of CWD is represented by lying and standing deadwood of Scots pine of the 2nd decay class. The average C stock in CWD is 9.2 t C ha-1 with a variation range from 1.7 to 14.3 t C ha-1. The study was conducted by the researchers of the Forest Research Institute of Karelian Research Centre RAS within the topic «Development of a system for land-based and remote monitoring of carbon pools and greenhouse gas flows in Russian Federation; providing for the creation of a data-registering system for recording data for climatically active substances and the carbon budget in forests and other terrestrial ecosystems» as part of the implementation of the most important innovative project of national importance (MIIPNI) «Unified national system for monitoring climatically active substances».